Issues Of Adapting The “Direct-Costing” Method For Considering Product Costs To The Practice Of The Country - Djumanov Saitmurod Alibekovich (Academia One Publishing, 2025)
In today's conditions of digitization and transformation, the activities of managing entities require criteria such as fairness, timeliness, neutrality, and accuracy in all processes related to economic information. Currently, the economic information obtained should fully meet the demands of internal and external users and should be generated with minimal labor and time expenditure. Providing information on costs and revenues for making tactical and strategic management decisions regarding the activities of various divisions of the enterprise allows for budgeting of financial and economic activities conducted in accordance with the company's accounting policy, analyzing investment projects, applying advanced methods for accounting costs and calculating product costs, preparing segment reports based on responsibility centers, and forming transfer prices used in transactions between internal business units
Keywords: responsibility; information; transformation